Effect of bit wear on hammer drill handle vibration and productivity. Issue 8 (3rd August 2017) - Antonucci, Andrea; Barr, Alan; Martin, Bernard; Rempel, David
ABSTRACT: The use of large electric hammer drills exposes construction workers to high levels of hand vibration that may lead to hand-arm vibration syndrome and other musculoskeletal disorders. The aim of this laboratory study was to investigate the effect of bit wear on drill handle vibration and drilling productivity (e.g., drilling time per hole). A laboratory test bench system was used with an 8.3 kg electric hammer drill and 1.9 cm concrete bit (a typical drill and bit used in commercial construction). The system automatically advanced the active drill into aged concrete block under feed force control to a depth of 7.6 cm while handle vibration was measured according to ISO standards (ISO 5349 and 28927). Bits were worn to 4 levels by consecutive hole drilling to 4 cumulative drilling depths: 0, 1, 900, 5, 700, and 7, 600 cm. Z-axis handle vibration increased significantly (p<0.05) from 4.8 to 5.1 m/s 2 (ISO weighted) and from 42.7–47.6 m/s 2 (unweighted) when comparing a new bit to a bit worn to 1, 900 cm of cumulative drilling depth. Handle vibration did not increase further with bits worn more than 1900 cm of cumulative drilling depth. Neither x- nor y-axis handle vibration was effected by bit wear. The time to drill a hole increased by 58% for the bit with 5, 700 cm of cumulative drilling depth compared to a new bit. Bit wear led to a small but significant increase in both ISO weighted and unweighted z-axis handle vibration. Perhaps more important, bit wear had a large effect on productivity. The effect on productivity will influence a worker's allowable daily drilling time if exposure to drill handle vibration is near the ACGIH Threshold Limit Value. [1] Construction contractors should implement a bit replacement program based on these findings.